Artikel Review : Studi Fitokimia dan Aktivitas Farmakologi pada Tumbuhan Kapulaga (Elletaria cardamomum (L.) Maton) - Zahwa Putri Pangestu Zahwa Putri Pangestu; Arista Wahyu Ningsih; Irvan Charles Sera Klau; Armeta Yuniar Pitaloka; Nura Wahidiyatur Rohmah; Fhinnishshia Gladys Sesi; Moh. Basri Firdaus Firman Norsyah (Program Studi Farmasi Fakultas Sains Kesehatan, 2023)
Cardamom is one of the medicinal plants that can produce essential oils and is included in the top 9 largest spice commodities in the world. As a world export commodity, cardamom is often traded in the form of essential oils and dried fruit forms. This review aims to provide information about phytochemical studies in cardamom and cardamom pharmacological studies to determine the content contained in cardamom. The method used in this article review uses the google scholar, Dimension, and PubMed websites. With the keywords cardamom, phytochemical content, morphology, and pharmacological activity of cardamom plants. In the cardamom plant content test, dragendorf and mayer solvents were used to check for the presence of alkaloid compounds, in the flavonoid examination, HCl, Mg, and amyl alcohol solvents were used, in the examination of tannin compounds, gelatin solvents were used, and in polyphenolic senaywa used FeCl 3 solvents to check the presence of polyphenolic compounds. The antimicrobial activity of cardamom plants is shown by the presence of sineol, terpineol, and alpha-borneol which can reduce bad breath and kill bacteria that cause dental plaque. Anti-inflammatory activity in cardamom plants can prevent and inhibit proinflammatory proteins through all inflammatory signaling pathways. In antioxidant activity there are several compounds including flavonoids that can increase antioxidant defenses and can reduce inflammation. Cardamom has compounds such as: alkaloids, flavonoids, tannins, polyphenolics, and saponins. Because of the presence of compounds contained in cardamom plants, there are several pharmacological activities, including: antimicrobial activity, antioxidant activity, and anti-inflammatory activity.